Relapse to opioid use in opioid-dependent individuals released from compulsory drug detention centres compared with those from voluntary methadone treatment centres in Malaysia: a two-arm, prospective observational study - Wegman, Martin P.; Altice, Frederick L.; Kaur, Sangeeth; Rajandaran, Vanesa; Osornprasop, Sutayut; Wilson, David; Wilson, David P.; Kamarulzaman, Adeeba (Elsevier, 2017)
Background Detention of people who use drugs into compulsory drug detention centres (CDDCs) is common throughout East and Southeast Asia. Evidence-based pharmacological therapies for treating substance use disorders, such as opioid agonist treatments with methadone, are generally unavailable in these settings. We used a unique opportunity where CDDCs coexisted with voluntary drug treatment centres (VTCs) providing methadone in Malaysia to compare the timing and occurrence of opioid relapse (measured using urine drug testing) in individuals transitioning from CDDCs versus methadone maintenance in VTCs. Methods We did a parallel, two-arm, prospective observational study of opioid-dependent individuals aged 18 years and older who were treated in Malaysia in the Klang Valley in two settings: CDDCs and VTCs. We used sequential sampling to recruit individuals. Assessed individuals in CDDCs were required to participate in services such as counselling sessions and manual labour. Assessed individuals in VTCs could voluntarily access many of the components available in CDDCs, in addition to methadone therapy. We undertook urinary drug tests and behavioural interviews to assess individuals at baseline and at 1, 3, 6, 9, and 12 months post-release. The primary outcome was time to opioid relapse post-release in the community confirmed by urinary drug testing in individuals who had undergone baseline interviewing and at least one urine drug test (our analytic sample). Relapse rates between the groups were compared using time-to-event methods. This study is registered at ClinicalTrials.gov (NCT02698098). Findings Between July 17, 2012, and August 21, 2014, we screened 168 CDDC attendees and 113 VTC inpatients; of these, 89 from CDDCs and 95 from VTCs were included in our analytic sample. The baseline characteristics of the two groups were similar. In unadjusted analyses, CDDC participants had significantly more rapid relapse to opioid use post-release compared with VTC participants (median time to relapse 31 days [IQR 26–32] vs 352 days [256–unestimable], log rank test, p<0·0001). VTC participants had an 84% (95% CI 75–90) decreased risk of opioid relapse after adjustment for control variables and inverse propensity of treatment weights. Time-varying effect modelling revealed the largest hazard ratio reduction, at 91% (95% CI 83–96), occurs during the first 50 days in the community. Interpretation Opioid-dependent individuals in CDDCs are significantly more likely to relapse to opioid use after release, and sooner, than those treated with evidence-based treatments such as methadone, suggesting that CDDCs have no role in the treatment of opioid-use disorders. Funding The World Bank Group, Doris Duke Charitable Foundation, National Institute on Drug Abuse, Australian National Health & Medical Research Council, National Institute of Mental Health, and the University of Malaya-Malaysian Ministry of Higher Education High Impact Research Grant.